The Content of The Operation Quality Concept of The Scientific and Technical Organization - Abdollovich Kremcheev, Eldar; Abdollovna Kremcheeva, Dinara (Opción, 2019)
This article highlights and clarifies the content of the basic concepts related to the quality assessment and satisfaction with the performance and products of the scientific and technical organization, as well as analyzes the generally accepted approaches and requirements of ISO 9000-2015 international standards to deter- mine the operation quality of the scientific and technical organization. The authors clarify and complement the quality concept of scientific and technical products through the extended characteristics of all parties concerned. Based on the con- ducted analysis, the quality of scientific and technical products is considered in a broader interpretation, as a service, which includes the quality of the scientific and technical activities outcome as well as the quality of support service. The ar- ticle highlights additional factors affecting the quality of products resulted from the scientific and technical operation of the organization. The authors consider the interrelation of categories such as “satisfaction” and “quality”. Special attention in the article is paid to the risk management as a necessary element of the quality management system.